Perspektif Posner, Rawls, dan Sen atas Program Koperasi Merah Putih dan Kawasan Wisata Halal - Andra Bani Sagalane; Sirot; Muhammad Hasyim; Ade Netra; Faisal Santiago (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
Community-based economic development programs, such as the Merah Putih Cooperative and Halal Tourism Zone in Jakarta, often rely on technical-instrumental approaches that lack a robust philosophical foundation, thereby imperiling their sustainability and equity. A significant gap persists between the constitutional ideal of cooperatives as the cornerstone of the Pancasila economy and the suboptimal reality of their implementation in delivering inclusive member welfare. This study aims to critically analyze these programs through the theoretical lenses of Richard A. Posner (economic efficiency), John Rawls (procedural justice), and Amartya Sen (capability empowerment) to construct a holistic and multidimensional evaluation framework. The research employs a qualitative method with a conceptual-philosophical study design. Data were collected through an in-depth literature review of the primary and secondary works of the three philosophers, alongside relevant policy documents. Data analysis was conducted using an interpretive-critical approach to synthesize these divergent perspectives. The findings reveal that integrating the three philosophies produces a tripartite evaluation framework composed of: operational efficiency (Posner), distributive and procedural justice (Rawls), and the expansion of members’ substantive freedoms (Sen). This synthesis demonstrates that a program’s success is not measured solely by the growth of cooperative assets, but more profoundly by the equitable distribution of benefits and the enhancement of members’ capabilities to live lives they have reason to value. In conclusion, community-based economic development necessitates a dynamic equilibrium between the instrument of efficiency, the morality of justice, and the ultimate goal of human empowerment.